Design and Construction of Novel Instrumentation for Low-Field MR Tomography - Gogola Daniel; Szomolanyi Pavol; Škrátek Martin; Frollo Ivan (Measurement Science Review, 2018)
Magnetic resonance imaging (MRI) is a very popular tool for diagnostic applications and research studies. Low-field MR scanners, usually with an open design, are suitable for claustrophobic and obese patients, as well as for children, who may be fearful in closed MR scanners. However, these types of scanners provide lower spatial resolution and a lower signal-to-noise ratio (SNR) if compared with the same examination performed at the same time at high field scanners. It is dominantly caused by the low field strength and other factors, such as radiofrequency noise. Therefore, a long measurement time is usually necessary. This research paper is focused on the development of novel probes and preamplifiers for low-field MR scanners to improve SNR, and thus, shorten the measurement time. In this study, we describe the design of a high impedance preamplifier and a high temperature superconductor (HTS) coil. This novel instrumentation was compared with uncooled and cooled copper coils. Improvement in SNR in the case of an HTS coil is reported.